English version of the food disgust scale: Optimization and other considerations. Issue 2 (3rd January 2021) - Thibodeau, Margaret; Yang, Qian; Ford, Rebecca; Pickering, Gary
Abstract: The disgust elicited by food plays an important role in food choice and consumption. Recently, Hartmann and Siegrist (Food Quality and Preference, 2018, 63, 38–50) developed and validated in German the food disgust scale (FDS), a 32‐item instrument designed to measure visceral disgust elicited by food. In Study 1, we tested the English language translation of the FDS and its shortened version (FDS‐SHORT) in England ( n = 85) and Canada ( n = 70). The internal reliability (Cronbach's alpha and mean interitem correlation [MCI]) was acceptable for both the FDS (α = .90, MIC = .22) and the FDS‐SHORT (α = .73, MIC = .25). Exploratory factor analysis revealed that the English and German versions of the FDS had similar underlying structure and good discriminant validity. In Study 2, female participants ( n = 159) who completed the FDS where the anchor term disgusted was used had higher FDS‐SHORT scores than either their male counterparts or females for whom the anchor term grossed out was used (F[2, 266] = 11.1, p < .001). As grossed out captures only visceral rather than moral disgust, we recommend its adoption in English versions of these scales. These studies confirm that, as modified, the English FDS and FDS‐SHORT are reliable and can be used with confidence in future research. Practical application: This study has further assessed and optimized an English translation of the food disgust scale, which will allow for its use by food researchers and practitioners in English‐speaking countries. The finding that food disgust scores vary with sex and culture provides guidance to producers and marketers of novel food products and flavors.